2019
DOI: 10.1002/ijc.32526
|View full text |Cite
|
Sign up to set email alerts
|

Results of API–AI based regimen in osteosarcoma adult patients included in the French OS2006/Sarcome‐09 study

Abstract: In the OS2006 study, patients younger than 18 years were treated with a methotrexate‐based regimen (MTX), patients older than 25 years with a doxorubicin–cisplatin–ifosfamide‐based regimen (API–AI), whereas patients aged 18–25 years received either API–AI or MTX. We herein report the prespecified subgroup analysis of the outcome of 106 patients treated with API–AI. Preoperative chemotherapy combined three doxorubicin–ifosfamide–cisplatin (API) and two doxorubicin–ifosfamide (AI) courses. Postoperative chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…[24][25][26][27] The doxorubicin/cisplatin/HD-MTX (MAP) regimen is most frequently used as front-line ChT in children and young adult patients; [24][25][26] however, HD-MTX can be challenging to administer in adults. 27,28 In patients aged over 40 years, the use of MTX (8 g/m 2 ) after a poor response to non-MTX induction ChT was proved to be feasible, and regimens combining doxorubicin, cisplatin and potentially ifosfamide are an alternative. [24][25][26]29 Most current protocols for localised disease include a period of preoperative ChT, to facilitate local surgical treatment and to allow the assessment of histological response, although there is no evidence to support a change in ChT based on this alone .…”
Section: Osteosarcomamentioning
confidence: 99%
“…[24][25][26][27] The doxorubicin/cisplatin/HD-MTX (MAP) regimen is most frequently used as front-line ChT in children and young adult patients; [24][25][26] however, HD-MTX can be challenging to administer in adults. 27,28 In patients aged over 40 years, the use of MTX (8 g/m 2 ) after a poor response to non-MTX induction ChT was proved to be feasible, and regimens combining doxorubicin, cisplatin and potentially ifosfamide are an alternative. [24][25][26]29 Most current protocols for localised disease include a period of preoperative ChT, to facilitate local surgical treatment and to allow the assessment of histological response, although there is no evidence to support a change in ChT based on this alone .…”
Section: Osteosarcomamentioning
confidence: 99%
“…The M-EI protocol is based on the randomized OS94 paediatric trial, which demonstrated that children and adolescent osteosarcoma patients receiving M-EI had a similar outcome as those receiving methotrexate combined with doxorubicin [128]. The adult API-AI protocol is based on a phase II trial showing that the API-AI group had similar response rates as a group receiving API-AI plus HDMTX [133], with similar findings reported in a phase III trial [134]. A recent French study reported that the M-EI and API-AI protocols yielded similar survival outcomes in 18-to 25-year-old patients, though histological response was better in the M-EI group (60%) than the API-AI group (41%) [132].…”
Section: Chemotherapymentioning
confidence: 86%
“…Centers reported 5‐year relapse/progression‐free (PFS) survival rates in patients with osteosarcoma ranging from 40% to 68% with various combinations of the other active drugs (Figure 3A,B; Table 3). 7,8,42–61 The initial proof of non‐HDMTX protocols came from the European Osteosarcoma Intergroup (EOI) trials. While the first EOI trial compared two‐drug protocol Adriamycin‐ cisplatin (AP) to AP with HDMTX, the second trial compared AP to a T10‐like multidrug protocol 48,62 .…”
Section: Systemic Therapy Evolution In Osteosarcoma ‐ Lmic Perspectivementioning
confidence: 99%
“…The other non‐HDMTX protocols (Table 3) are the French AP–ifosfamide (API)‐Adriamycin ifosfamide (AI) 56,57 ; German AP–vincristine (V)‐cyclophosphamide (CTX) 55 ; the MD Anderson AP–AI (good responders) with additional HDMTX (poor responders) 64 ; the St. Judes OS99 and OS91 with ifosfamide Adriamycin (IA)–carboplatin (C) and IA–C with HDMTX 53,65 ; and Brazilian IC–epirubicin(Epi)) with HDMTX for poor responders and AP alternating with high‐dose ifosfamide 59, 66 and other Epi‐based protocols 67 …”
Section: Systemic Therapy Evolution In Osteosarcoma ‐ Lmic Perspectivementioning
confidence: 99%